Compression after impact strength of repaired GFRP composite laminates under repeated impact loading. (1st December 2015) - Jefferson Andrew, J.; Arumugam, V.; Saravanakumar, K.; Dhakal, H.N.; Santulli, C.
Abstract: During their service life, composite materials are prone to damage, which compromises their structural performance significantly. In this study, glass/epoxy composite specimens fabricated using hand layup method and further cured in a compression molding machine were cut from the laminates and subjected to low velocity impact damage in order to investigate the effects of repair. The impacted laminates were repaired by removing the damage area with a circular cutout and filled with a chopped short Kevlar/epoxy: the efficiency of the repair procedure and toughness of the repaired laminates were examined by repeated impacts on the repaired site. The residual strength of the post impacted repaired laminates is investigated by the conduction of compression after impact (CAI) loading with acoustic emission monitoring (AE) technique. The structural performance of both repaired and unrepaired laminates are compared and discussed.